2020
DOI: 10.1101/2020.09.30.320762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hallmarks ofAlpha- andBetacoronavirusnon-structural protein 7+8 complexes

Abstract: Coronaviruses infect many different species including humans. The last two decades have seen three zoonotic coronaviruses with SARS-CoV-2 causing a pandemic in 2020. Coronaviral non-structural proteins (nsp) built up the replication-transcription complex (RTC). Nsp7 and nsp8 interact with and regulate the RNA-dependent RNA-polymerase and other enzymes in the RTC. However, the structural plasticity of nsp7+8 complex has been under debate. Here, we present the framework of nsp7+8 complex stoichiometry and topolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
(97 reference statements)
2
15
1
Order By: Relevance
“…The recent optimization of robust high-throughput chromatographic methods and fast sample preparation protocols has already shown great promise in different fields, and will likely also enter diagnostic and prognostic pipelines in the clinical setting for infectious diseases. So far, top-down and structural MS approaches have focused on purified assemblies, showing the potential for deducing the determinants of viral protein complex formation [ 25 ]. Moreover, the field is moving towards an analysis of crude extracts in native MS, combinations of labeling and top-down approaches, as well as in situ labelling combined with MS, allowing for the profiling of complete structural networks [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent optimization of robust high-throughput chromatographic methods and fast sample preparation protocols has already shown great promise in different fields, and will likely also enter diagnostic and prognostic pipelines in the clinical setting for infectious diseases. So far, top-down and structural MS approaches have focused on purified assemblies, showing the potential for deducing the determinants of viral protein complex formation [ 25 ]. Moreover, the field is moving towards an analysis of crude extracts in native MS, combinations of labeling and top-down approaches, as well as in situ labelling combined with MS, allowing for the profiling of complete structural networks [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The order of processing was identified from the intermediate polyprotein products nps7–8 and nsp7–9, which provided much higher precision than e.g., SDS-PAGE (sodium dodecyl sulphate–polyacrylamide gel electrophoresis) performed for comparison. In a follow-up [ 25 ], nsp7+8 complexes from different alpha- and betacoronaviruses, including SARS-CoV-2, showed variability in stoichiometry and topology, hence pointing to distinct assembly pathways. Notably, few amino acid exchanges in nsp8 and nsp7 determine stoichiometry switching.…”
Section: Top-down Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nsp7-nsp7 interaction is however consistent with formation of a (nsp7-nsp8) 2 heterotetramer 16,17 and its dissociation into a stable nsp7-nsp8 heterodimer that was suggested to bind nsp12 18 .…”
mentioning
confidence: 81%
“…Mutations to Alanine in nsp7 residues K7, H36 and N37 reduced RNA binding by the nsp7+nsp8+nsp12 complexes, polymerase processivity and viral replication 6 . All these results suggested that nsp7 may play a crucial, yet intriguing role(s) in coronavirus replication 8 . On the other hand, for optimal RNA binding and processivity, the nsp12 requires not only the presence of nsp7+nsp8 but also other nsps.…”
Section: Introductionmentioning
confidence: 87%